2022
DOI: 10.1111/ejn.15768
|View full text |Cite
|
Sign up to set email alerts
|

The influence of phoneme contexts on adaptation in vowel‐evoked envelope following responses

Abstract: Repeated stimulus presentation leads to neural adaptation and consequent amplitude reduction in vowel-evoked envelope following responses (EFRs)-a response that reflects neural activity phase-locked to envelope periodicity.EFRs are elicited by vowels presented in isolation or in the context of other phonemes such as consonants in syllables. While context phonemes could exert some forward influence on vowel-evoked EFRs, they may reduce the degree of adaptation. Here, we evaluated whether the properties of conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 47 publications
0
8
2
Order By: Relevance
“…They used speech-shaped noise as the preceding masker for EFRs elicited by /a/ in /da/ and demonstrated delayed peak latencies in masked conditions. The present study results are, however, inconsistent with Easwar et al (2021) who found no statistically significant effects of the surrounding context on EFRs elicited by a wide range of vowels. The discrepancy between the present study and Easwar et al (2021) could be due to the characteristics of the context as well as the EFR stimulus.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…They used speech-shaped noise as the preceding masker for EFRs elicited by /a/ in /da/ and demonstrated delayed peak latencies in masked conditions. The present study results are, however, inconsistent with Easwar et al (2021) who found no statistically significant effects of the surrounding context on EFRs elicited by a wide range of vowels. The discrepancy between the present study and Easwar et al (2021) could be due to the characteristics of the context as well as the EFR stimulus.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study results are, however, inconsistent with Easwar et al (2021) who found no statistically significant effects of the surrounding context on EFRs elicited by a wide range of vowels. The discrepancy between the present study and Easwar et al (2021) could be due to the characteristics of the context as well as the EFR stimulus. The contexts were higher in level and longer in duration in the present study, which may have led to increased chances of forward masking (Lasky & Rupert 1982; Kramer & Teas 1982).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations